2001
DOI: 10.1074/jbc.m009822200
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic and Nonmutagenic Bypass of DNA Lesions byDrosophila DNA Polymerases dpolη and dpolι

Abstract: cDNA sequences were identified and isolated that encode Drosophila homologues of human Rad30A and Rad30B called drad30A and drad30B. Here we show that the C-terminal-truncated forms of the drad30A and drad30B gene products, designated dpol⌬C and dpol⌬C, respectively, exhibit DNA polymerase activity. dpol⌬C and dpol⌬C efficiently bypass a cis-syn-cyclobutane thymine-thymine (TT) dimer in a mostly error-free manner. dpol⌬C shows limited ability to bypass a 6 -4-photoproduct ((6 -4)PP) at thymine-thymine (TT-(6 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 44 publications
5
30
0
Order By: Relevance
“…For ex- ample, the motif SRGVLSFF (in which the conserved residues are indicated in bold) is present in residues 540 -547 of human POL and may contribute to PCNA binding (34). Another study has shown that the localization of POL protein in the nucleus requires sequences within amino acids 219 -451, and sequences within amino acids 492-539 and 636 -715 are critical for interaction between POL and POL proteins (35,36). The results in Fig.…”
Section: Among All Of the Annotated Genes In Thementioning
confidence: 60%
“…For ex- ample, the motif SRGVLSFF (in which the conserved residues are indicated in bold) is present in residues 540 -547 of human POL and may contribute to PCNA binding (34). Another study has shown that the localization of POL protein in the nucleus requires sequences within amino acids 219 -451, and sequences within amino acids 492-539 and 636 -715 are critical for interaction between POL and POL proteins (35,36). The results in Fig.…”
Section: Among All Of the Annotated Genes In Thementioning
confidence: 60%
“…Polη is known to specifically bypass UV-induced lesions in yeast and mammals, and dPolη has been shown to synthesize efficiently past cyclobutane pyrimidine dimers in vitro (Ishikawa et al, 2001;Johnson et al, 1999;McCulloch et al, 2004;McDonald et al, 1997). We therefore tested the sensitivity of embryos from Exc2.15 -derived embryos (Fig.…”
Section: Drosophila Y-family Polymerases Are Expressed In Early Embryosmentioning
confidence: 99%
“…dPolη and dPolι are functional translesion polymerases in vitro (Ishikawa et al, 2001). dPolη larvae exhibit increased sensitivity to UV irradiation, and homologous recombination is impaired in dPolη flies (Kane et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drosophila constructs-Rev1 was amplified by RT-PCR of total RNA prepared by Trizol extraction of Kc cells and cloned into pACT2. Polη and Polι were amplified from pGEXdPolι and pGEX-dPolι [20] and cloned into pGBKT7. Rev7 was amplified by RT-PCR and cloned into pGBKT7.…”
Section: Pair-wise Yeast Two-hybrid Assays and Interaction Domain Mapmentioning
confidence: 99%